A „belső ember” faggatása mint a terápiás írás és az önszupervízió keresztyén formája - MIKOLA NYÍRI, Emese (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Interrogating the “Inner Man” as a Christian Method of Therapeutic Writing and Self-supervision. Augustine served as an example for the foundations of Christian writing therapy, since he created the tradition of written confessions, as well as making reflections on it. In this study, we present Augustine's concept of the inner man viewed from the context of Christian writing therapy, with the aim of providing assistance for therapeutic writing and one of its essential areas of application for self-supervision, which is essential in all helping professions in addition to supervision.